AN ANALYSIS OF HOUSEHOLD RESILIENCE AND DIVORCE WITHIN MUSLIM FAMILIES AMIDST THE COVID-19 PANDEMIC - Akmal Tarigan, Azhari (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2023)
This study aims to examine the factors behind the increasing of divorce cases amidst the COVID-19 Pandemic. This study followed a qualitative research method with case study approach to analyse the factors behind the increasing of divorce cases within Muslim families in North Sumatra amidst the COVID-19 Pandemic. The findings of this study indicate that economic factors, third-person influence, lack of honesty, domestic violence, and inequality in child care are main factors that increase the cases of divorce. The COVID-19 pandemic is not the main factor in the occurrence of divorce, however, this pandemic is another factor that increases the risk of divorce, especially related to economic problems when the problem is not communicated properly. This study shows the importance to strengthen the dimensions of family life by ensuring the establishment of a more harmonious family life, understanding and supporting each other to develop household resilience amidst the COVID-19 pandemic.